Transendensi Tasawuf: Mencari Ketenangan Jiwa Dalam Tradisi Spiritual Masyarakat Bengkulu - Ulfa, Fadillah; Desi Firmasari (Taqrib : Journal of Islamic Studies and Education, 2025)
This study aims to explore the role of Sufism in achieving inner peace among the people of Bengkulu, focusing on spiritual practices such as dhikr, tafakur, and muhasabah. The novelty of this research lies in the in-depth examination of the application of Sufism in the daily lives of the Bengkulu community, which has been underexplored, and its impact on mental and spiritual well-being. A qualitative approach is used, with in-depth interviews and observations of spiritual activities in mosques, pesantren, and study groups. Data is analyzed thematically to identify patterns in the relationship between Sufism and inner peace. The findings show that Sufism practices in Bengkulu significantly contribute to reducing anxiety and stress and enhancing inner peace, particularly through dhikr and tafakur performed in community settings. The people of Bengkulu report feeling calmer and more patient after regularly practicing Sufism. However, the study also identifies barriers such as urban life pressures, time constraints, and the influence of technology that reduce the effectiveness of Sufi practices. This research contributes to a deeper understanding of Sufism in the context of urban communities.